The Effect of Combination of Buteyko Breathing Technique and Walking Exercise on Forced Peak Expiratory Flow In Adult Asthmatic Patients - Wiwik Udayani; Muhammad Amin; Makhfudli M (Faculty of Nursing Universitas Padjadjaran, 2019)
The Buteyko technique can reduce asthma symptoms, reduce the use of bronchodilators but few and not significant in reducing bronchial responsiveness. Physical exercise that complements breathing exercises in pulmonary rehabilitation can improve pulmonary physiology and control asthma. Physical exercise in the form of walking can improve pulmonary physiology and asthma control by reducing hyperesponsivity reactions and increasing cardiorespiratory endurance. But the combination of these two exercises has never been studied. The objective of this study was to analyze the effect of a combination of Buteyko breathing techniques and walking exercises on Peak Forced Expiration Flow. The design of this study was quasi experimental with pretest-posttest control group design. The location of the study was in the pulmonary clinic of Regional General Hospital of Sidoarjo Regency and Bangil Regional General Hospital in Pasuruan Regency, East Java. Respondents were selected by randomization by simple random sampling. Respondents in this study amounted to 76 respondents. Forced Expiration Peak Flow Data is measured using a peak flow meter. The intervention group was given a combination exercise with Buteyko breathing technique and walking exercise for 8 weeks, 3x per week, 55 minutes every training session. Giving a combination of Buteyko breathing technique and walking exercises using module and video media. FPEF measurements were carried out 3 times (pretest, week 4, week 8). Data were analyzed using SPSS 22 with GLM-RM (General Linear Model-Repeated Measure) ANOVA. The results showed a significant difference in the FPEF rate between before and after 4 weeks and 8 weeks of the combination intervention of the Buteyko breathing technique and walking exercises in the treatment group with (p <0.05) with p = 0.000. The findings indicate that breathing exercises and physical exercise through a combination of Buteyko breathing techniques and walking exercise can increase the FPEF rate through the mechanism of increasing CO2 and producing nitric oxide which has bronchodilation effects and through decreasing inflammatory mediators so that it can reduce asthma symptoms.This exercise can be used as an alternative choice in supporting pharmacological therapy to improve FPEF.